2018
DOI: 10.28945/3954
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Psychological Benefits of Using an Emerging Video Technology to Coach and Retain Doctoral Learners

Abstract: Aim/Purpose: Retention of doctoral students, particularly during the dissertation stage, has been a decades-old concern. The study examined the value of dissertation chairs’ use of a cloud-based video technology for coaching doctoral students, and its influence on psychological factors previously linked to retention. The psychological aspects included social presence, research self-efficacy, social isolation, and motivation Background: Prior research identified the importance of addressing psychological facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(129 reference statements)
0
13
0
Order By: Relevance
“…Many studies focused on the use of video-conferencing tools (E.g., Anastasiades et al, 2010;Candarli & Yuksel, 2012;Delaney et al, 2004;Ghazal et al, 2015;Karal et al, 2011;Knipe & Lee, 2002;Mader & Ming, 2015;Oh & Lee, 2012). Some studies focused specifically on the use of Zoom in the classroom (E.g., Archibald et al, 2019;Maul et al, 2018;Sayem et al ,2017;Wang et al, 2018). Over the past few months in particular, researchers have started investigating online learning during the COVID-19 Pandemic (Adnan & Anwar, 2020;Agarwal & Kaushik, 2020;Basilaia et al, 2020;Bao, 2020;Demuyakor, 2020;Murphy, 2020;Naciri et al, 2020;Toquero, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focused on the use of video-conferencing tools (E.g., Anastasiades et al, 2010;Candarli & Yuksel, 2012;Delaney et al, 2004;Ghazal et al, 2015;Karal et al, 2011;Knipe & Lee, 2002;Mader & Ming, 2015;Oh & Lee, 2012). Some studies focused specifically on the use of Zoom in the classroom (E.g., Archibald et al, 2019;Maul et al, 2018;Sayem et al ,2017;Wang et al, 2018). Over the past few months in particular, researchers have started investigating online learning during the COVID-19 Pandemic (Adnan & Anwar, 2020;Agarwal & Kaushik, 2020;Basilaia et al, 2020;Bao, 2020;Demuyakor, 2020;Murphy, 2020;Naciri et al, 2020;Toquero, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They identified the following reasons for that: relative ease of use, cost-effectiveness, data management features, and security options. Maul et al (2018) investigated the perceived value of the use of Zoom for dissertation chairs to coach and mentor doctoral students. The participants of this study were dissertation chairs and students in the College of Doctoral Studies at a university in the southwestern United States.…”
Section: Introductionmentioning
confidence: 99%
“…This application enables many people to see each other at the same time. Maul, Berman, & Ames (2018) mention that the use of Zoom application affects students psychologically, which contributes to the increase in their learning motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as the frequency of synchronous communication increased so did students' program integration. Technologies offer opportunities for sustained communication and interaction between faculty and students (Rockinson-Szapkiw, et al, 2010); therefore, integration in an online course can be supported through the frequent use of synchronous web technologies, such as video conferencing software as previous research has found (Maul et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, online doctoral students in other studies have reported that balanced use of both synchronous and asynchronous communication enhanced their sense of connection with faculty and peers, and ultimately, persistence (Teng, Chen, Kinshuk, & Leo, 2012;Fuller, Risner, Lowder, Hart, & Bachenheimer, 2014). Maul, Berman, and Ames (2018), in an exploratory case study of online doctoral programs (e.g., DBA, EdD, and PhD) in the dissertation phase, found that the use of online video coaching improved academic success, belonging and integration, and ultimately retention. The researchers also noted that the frequency of use may influence a doctoral students' success.…”
Section: Program Factorsmentioning
confidence: 93%